Characterization of the molecular mechanisms underlying retinoic acid induced growth inhibition in MCF-7 human breast cancer cells. - Teixeira, Christine. (University of Ottawa (Canada), 1999)
Retinoids are known to strongly inhibit the growth of estrogen (E2) dependent human breast cancer cells. This growth inhibition was found to be associated with an accumulation of cells in G1 phase of the cell cycle. Since the molecular mechanisms underlying these antiproliferative effects were unknown, we investigated the effects of retinoic acid (RA) on cell cycle progression and the expression and activity of cell cycle regulatory genes in the E2 dependent breast carcinoma cell line, MCF-7. We have found that RA induced accumulation of cells in G1 was correlated with decreased phosphorylation of the retinoblastoma protein (pRb). It also resulted in a down regulation of cyclin dependent kinase 2 (cdk2) and cyclin D1 gene expression and a profound down regulation of cdk2 activity. In contrast, no changes were seen in cdk4 expression or activity. We have further demonstrated that RA did not cause a change in the overall levels of expression of the known cyclin-cdk inhibitors p21 and p27. As well, no change in the activity of the cdk activating kinase, CAK, was detected. These results suggest that the growth inhibition of MCF-7 cells is associated with a down regulation of cdk2 activity. While this reduced activity occurred in the absence of RA-mediated increases in the levels of the cdk inhibitors p21 and p27, an increased association between p27 and cdk2 was observed in RA treated lysates. Furthermore, assays of cdk2 in pooled lysates taken from RA treated and control cells showed that RA treated cells contain a p27-like transferable cdk2 inhibitory activity. Pretreatment of cells with antisense but not mismatch p27 oligonucleotides attenuated the inhibitory effects of RA on cdk2 associated activity. These findings demonstrate that RA is capable of regulating cdk2 activity through a mechanism involving p27. RA also caused an increase in p53, we therefore investigated the role of p53 in growth arrest induced by exposure to RA. MCF-7/E6 cells expressing the human papillomavirus HPV16 E6 protein contained very low levels of p53 and exhibited partial abrogation of both cdk2 inactivation and G1 arrest in response to RA. To further elucidate the role of p53 in RA mediated inhibition of cdk2, MCF-7 cells were transfected with various p53 mutant expression constructs. However, none of the stable clones generated were impaired in their ability to down regulate cdk2 or undergo G1 arrest in response to RA. These results suggest that no functional domain of p53 alone contributes to the RA induced regulation of cdk2, but rather the cooperation of several domains of p53 may be required. We also observed that RA was able to profoundly down regulate cdk2 gene expression. However, following exposure to RA, no decrease in cdk2 gene transcription was observed in MCF-7 cells which had been stably transfected with a cdk2 promoter firefly luciferase reporter gene construct. These results were confirmed by nuclear run off assays which demonstrated that RA did not cause a decrease in the rate of cdk2 gene expression. Instead we found that RA decreased cdk2 expression by triggering posttranscriptional destabilization of the mRNA. Taken together, these findings suggest that RA inhibits cell cycle progression in MCF-7 cells through the inactivation of cdk2. Several targets have been identified that participate in the RA mediated down regulation of cdk2 activity.
Keywords: Biology, Molecular.